Synthesis of belite cement from lignite fly ash - K. Pimraksa (2018)
Synthesis of belite cement from lignite fly ash is studied as it can be produced using low temperature between 750 and 1200 °C leading to energy saving and low carbon dioxide emission. Two synthesis methods viz., clinkerization and hydrothermal processes assisted by calcinations are studied. Lignite fly ash is used as a main starting material. For the clinkerization process, the firing temperatures, types of additives and calcium oxide/silicon dioxide ratios (Ca/Si) are studied. In this process, the reaction between fly ash and calcium carbonate produces gehlenite (2CaO·Al2O3·SiO2) which is undesirable due to its poor hydraulic property. A slightly higher belite (2CaO·SiO2) phase is obtained using sulfate ion as a dopant and using high Ca/Si ratio. The strength of gehlenite bearing belite cement is, however, rather poor. For the hydrothermal-calcination process, the alkaline concentrations and calcining temperatures are studied. The final products are belite phase and mayenite (12CaO·7Al2O3) which are desirable as they possess hydraulic properties. The reasonable 28-day compressive strength of the belite cement mortar of 9.5 MPa is obtained. The hydrothermal process assisted by calcination is, therefore, suitable for use in the synthesis of belite cement from lignite fly ash. © 2009 Elsevier Ltd and Techna Group S.r.l.